Arthroscopic Repair Technique of Lateral Meniscus Tear at the Popliteal Hiatus Area - Qinwen Li, M.M.; Man Qiu, M.M.; Shixin Nie, M.D.; Fuling Chen, M.M.; Xuming Wang, M.M.; Hua Zhang, M.D. (Arthroscopy Techniques, 2025)
Arthroscopic treatment of lateral meniscus tear at popliteal hiatus area remains challenging due to the complex anatomy of the popliteal hiatus and limited operating space of the lateral compartment. Subtle injuries to attachments of the popliteal hiatus may be overlooked. Thus, this article presents an all-inside suture technique stitching the torn lateral meniscus to popliteomeniscal fascicles that avoids leaving the lateral meniscus unstable in at popliteal hiatus area postoperatively. Concern about entrapping the popliteal tendon or all-inside meniscus suture anchor migration in the joint cavity is not necessary.